2019
DOI: 10.35530/it.070.03.1560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of waste cotton usage on properties of OE-rotor yarns and knitted fabrics

Abstract: The use of recycled materials has gained massive importance in textile sector as well as in other sectors as the effects of reduction of natural sources are felt all over the world. In this study, it was aimed to analyse the effects of recycled cotton usage on properties of OE-rotor spun yarns and knitted fabrics produced from these yarns. For this purpose, OE-rotor yarns were produced at different proportion levels of virgin cotton and waste cotton that derived from blowroom 25%, 50%, 75%, 100%, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…3,4,21,22 The quality of production waste is better in comparison with post-production waste mainly in terms of fiber length and its variability. 1822 Many authors 122 concentrate on the quality of fibrous material components at the beginning of the process by the standard parameters used for definition of cotton fibers. On the other hand, they do not indicate the quality of fibrous materials from the point of view of amount of neps, dust, and impurities amount.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,21,22 The quality of production waste is better in comparison with post-production waste mainly in terms of fiber length and its variability. 1822 Many authors 122 concentrate on the quality of fibrous material components at the beginning of the process by the standard parameters used for definition of cotton fibers. On the other hand, they do not indicate the quality of fibrous materials from the point of view of amount of neps, dust, and impurities amount.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated how to optimally blend and reuse various production cotton waste, mainly carding stipes with addition of noils, and if necessary virgin cotton or polyester to get the high or regular quality of yarns has been demonstrated. 2,[6][7][8][9][10][11] The study on processing of cotton ginning waste into openend rotor yarn is presented in the literature 12,13 as is the processing of fully recycled fibers from fabric scraps. [14][15][16] The verification of suitable setting of the production line and selection of machine parts relevant for processing of cotton waste was also proven.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yarn and fabrics produced from 100% cotton gave the best results among all samples. The results of the study revealed that the use of recycled cotton in up to 75% of the mixture did not make a significant difference in the results [30].…”
Section: Ute Et Al Produced Single Jersey Knitted Fabricsmentioning
confidence: 83%
“…Liu et al [13] studied the production of regenerated cellulosic fi bers from Co waste. Halimi et al [14][15], Hasani and Tabatabaei [16], Wanassi et al [17], and Kılıc et al [18] investigated the recycling of Co fi bers from waste Co yarns.…”
Section: Introductionmentioning
confidence: 99%